2017
DOI: 10.5688/ajpe816104
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspectives on Interprofessional Teamwork Before and After an Interprofessional Pain Education Course

Abstract: Objective. To evaluate changes in pharmacy and nursing student perspectives before and after completion of an interprofessional education (IPE) course. Methods. A pre-and post-perception scale descriptive prospective study design utilizing Interdisciplinary Education Perception Scale (IEPS) and Collaboration and Satisfaction about Care Decisions (CSACD) with self-reported statements of knowledge and importance of professional roles was used. Results. Significant improvement was shown for IEPS and CSACD overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 25 publications
0
16
0
7
Order By: Relevance
“…A significant positive shift in the pain knowledge and attitudes toward collaboration has been demonstrated through IPE. 14 , 28 Simko et al 29 reported an increased knowledge and understanding of the importance of other profession's role in pain management in an IPE course for nursing and pharmacy students. Other studies have reported high student satisfaction and significant improvement in self-efficacy 1 as well as respect for each other's roles and responsibilities.…”
Section: Outcomes Of Interprofessional Educationmentioning
confidence: 99%
“…A significant positive shift in the pain knowledge and attitudes toward collaboration has been demonstrated through IPE. 14 , 28 Simko et al 29 reported an increased knowledge and understanding of the importance of other profession's role in pain management in an IPE course for nursing and pharmacy students. Other studies have reported high student satisfaction and significant improvement in self-efficacy 1 as well as respect for each other's roles and responsibilities.…”
Section: Outcomes Of Interprofessional Educationmentioning
confidence: 99%
“…There are a number of recent publications evaluating interprofessional pain management activities and courses using various methodologies, including clinically based small group tutorials, small group assignments, projects, large group workshops, and simulations (Hunter et al, 2015;Simko et al, 2017;Hadjistavropoulos et al, 2015;Ottis et al, 2016). The number of professions involved in these activities ranged from two to eight.…”
Section: Discussion (Act)mentioning
confidence: 99%
“…2,15 Previous research has demonstrated that interprofessional simulation programs embedded into curriculum can assist students' understanding of the scope of practice, roles, functions and responsibilities of other healthcare professionals; and instil respect and improve communication between healthcare professional students and patient safety. 5 Furthermore, extensive research investigating student and practitioners attitudes, 7,[16][17][18][19] readiness for interprofessional education [20][21][22][23] and perceptions of its perceived value exist in the literature. 19 Despite extensive literature on interprofessional education, particularly with respect to medical and nursing students, there have been relatively limited studies involving pharmacy and nursing students utilizing simulation laboratories and/or strategies; 5,[24][25][26] and a paucity of evidence related to simulation based interprofessional programs investigating perceptions and/or outcomes of collaborative decision-making between healthcare professional students.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…5 Furthermore, extensive research investigating student and practitioners attitudes, 7,[16][17][18][19] readiness for interprofessional education [20][21][22][23] and perceptions of its perceived value exist in the literature. 19 Despite extensive literature on interprofessional education, particularly with respect to medical and nursing students, there have been relatively limited studies involving pharmacy and nursing students utilizing simulation laboratories and/or strategies; 5,[24][25][26] and a paucity of evidence related to simulation based interprofessional programs investigating perceptions and/or outcomes of collaborative decision-making between healthcare professional students. 26 To our knowledge there are few studies to date that investigate pharmacy students' perceptions working together with other healthcare students utilizing simulation laboratories to "replicate" a real-life clinical environment to develop collaborative clinical decision-making skills.…”
Section: A C C E P T E Dmentioning
confidence: 99%